Mindful paths to food waste reduction: exploring the associations between gratitude, mindful eating behavior, and motivations for food waste avoidance - Giannou, Kyriaki; Mantzios, Michail (Frontiers in Psychology, 2026)
Past research has emphasised the potential of gratitude in reducing food waste by prompting behavioral changes. A critical question, however, remains: can individuals experience gratitude without being attentive to the food they consume, and what are the implications for food waste? The present study investigated how gratitude influences motivations for food waste avoidance, and examined the moderating role of mindful eating as an agent of attentiveness. One hundred and sixty-nine UK adults completed self-report measures on mindful eating behavior, gratitude and food avoidance motives, and the results showed positive correlations between gratitude and moral and financial motivations to avoid food waste, as well as between mindful eating behavior and all motivations to avoid food waste. A moderation analysis showed that overall mindful eating behavior did not significantly moderate the relationship between gratitude and motivations to avoid food waste. Findings highlight the important associations between psychological and behavioral resources (i.e., gratitude and mindful eating) and the formation of motivations related to sustainable food practices. Implications for future research are discussed.